Alloying effects of Fe and Al on formation and decomposition temperatures of vanadium hydride, V2H. (31st August 2017) - Kawai, R.; Yukawa, H.; Suzuki, A.; Nambu, T.; Murata, Y.
Abstract: The alloying effects of iron and aluminum on the formation and decomposition temperatures of vanadium hydride, β phase, have been investigated by a series of in - situ X-ray diffraction measurements in hydrogen atmosphere. It is found that the addition of iron increases the formation temperature of β phase, while the addition of aluminum decreases the formation temperature drastically. According to the first principal calculations, the addition of iron, chromium or nickel increases the hydrogen dissolution energy when hydrogen atom is inserted to the nearest neighbor site of alloying element. These results is considered to correspond to the increase in the plateau pressure of α–β phase transition by the addition of these alloying elements. The alloying effect on the change in the total energy upon hydrogen insertion into T-site is larger than O-site. As a result, the energy difference between T-site model and O-site model becomes small by the addition of these alloying elements, which will lead to increase the formation temperature of β phase. Aluminum in vanadium shows strong repulsive interaction with hydrogen so that hydrogen cannot occupy the nearest neighbor sites of aluminum energetically. Owing to this blocking effects, the formation temperature of β phase may decreases drastically by the addition of aluminum into vanadium. Highlights: The addition of Fe into V increases the hydride formation temperature. In contrast, the addition of Al into V decreases the formation temperature drastically. The addition of at least 3.5 mol% Al into V will suppress the hydride formation under one atm of hydrogen even at room temperature. Alloying effects on the phase stability of vanadium hydride are discussed based on a series of first principal calculations.